The Organizational Communication Perspective Theory - Kristina (Journal of Social Science, 2020)
Public sector organizations are undergoing a transformation in management style. Not only is the behavior of government agencies increasingly being carried out like business, where managers play a central role, but aspects of client service are also becoming more important. Communication is input or message from one person to another. Organizations need communication to streamline their work and carry out tasks in a perfect way. Communication is the art of sending messages and receiving the same in the form of feedback. The success of an organization is highly dependent on effective organizational communication patterns. This study aims to understand communication in achieving the objectives of government organizations. Furthermore, this study discusses effective communication in government organizations. Keywords: Organization Communication, Internal and External.